Astragaloside IV improves slow transit constipation by regulating gut microbiota and enterochromaffin cells - Wan, Xingyang; Zhou, Qian; Chen, Huaxian; Li, Zhen; Mo, Mianling; Liu, Zhimin; Zhang, Heng; He, Zhuojie; Xiao, Guozhong; Zheng, Yihui; Lin, Hongcheng; Ren, Donglin (Frontiers in Pharmacology, 2023)
Purpose: Slow transit constipation (STC) is a common gastrointestinal disorder characterized by altered gut microbiota and reduced number of enterochromaffin cells (ECs). Astragaloside IV (AS-IV), a low drug permeability saponin, has showed beneficial effects on patients with STC. However, the specific mechanism by which AS-IV regulates STC remains unclear. In this study, we aimed to investigate the effect of AS-IV on STC and its associated mechanisms involving gut microbiota.The effect of AS-IV on STC was evaluated on STC mice induced with loperamide. We measured defecation frequency, intestinal mobility, ECs loss, and colonic lesions in STC mice treated with AS-IV. We also analyzed the changes in gut microbiota and metabolites after AS-IV treatment. Moreover, we investigated the relationship between specific gut microbes and altered fecal metabolites, such as 3-bromotyrosine (3-BrY). We also conducted in vitro experiments to investigate the effect of 3-BrY on caspase-dependent apoptosis of ECs and the activation of the p38 MAPK and ERK signaling pathways induced by loperamide.Results: AS-IV treatment promoted defecation, improved intestinal mobility, suppressed ECs loss, and alleviated colonic lesions in STC mice. AS-IV treatment also affected gut microbiota and metabolites, with a significant correlation between specific gut microbes and altered fecal metabolites such as 3-BrY. Furthermore, 3-BrY may potentially reduce caspase-dependent apoptosis of ECs and protect cell survival by inhibiting the activation of the p38 MAPK and ERK signaling pathways induced by loperamide.Our findings suggest that changes in gut microbiota and ECs mediated the therapeutic effect of STC by AS-IV. These results provide a basis for the use of AS-IV as a prebiotic agent for treating STC. The specific mechanism by which AS-IV regulates gut microbiota and ECs warrants further investigation.